473 Propensity-matched comparison of left atrial appendage occlusion and direct oral anticoagulation for thromboembolic prevention in octogenarians. (8th December 2021) - Magnocavallo, Michele; Della Rocca, Domenico Giovanni; Lavalle, Carlo; Chimenti, Cristina; Carola, Gianni; Mohanty, Sanghamitra; Trivedi, Chintan; Bassiouny, Mohamed; Al-Ahmad, Amin; Burkhardt, David J; Gallinghouse, Joseph G; Sanchez, Javier E; et al.
Abstract: Aims: A significant amount of atrial fibrillation patients does not receive appropriate anticoagulation, owing to contraindications and side effects. Octogenarians have higher competing comorbidities with a remarkable bleeding/thromboembolic (TE) risk. We aimed at analysing the clinical outcomes of LAAO compared with direct oral anticoagulation (DOAC) in octogenarians. Methods and results: Data were extracted from two prospective databases including 488 LAAO and 825 DOAC patients. Patients aged 80 years or older accounted for 37.1% ( n = 181) and 39.5% ( n = 326). In order to attenuate the imbalance in covariates between the groups, a propensity score matching technique was used (covariates: age, sex, CHA2DS2-VASc, and HAS-BLED scores, follow-up duration; tolerance 0.02). This method resulted in matched populations with 108 octogenarian patients per group. The annual stroke/transient ischaemic attack (TIA) risk was estimated based on the CHA2DS2-VASc, and compared to the annualized observed risk, owing to calculate the % risk reduction associated with the two treatment strategies. A total of 216 octogenarians were included in the analysis (84 ± 3 years; CHA2DS2-VASc: 4.9 ± 1.4, HAS-BLED: 3.1 ± 0.9). A Watchman device was successfully deployed in all LAAO ≥ 80 patients; periprocedural adverse events were observed in 2.8% ( n = 3) of LAAO patients. During a follow-up of 13 ± 4 months, 3 (2.8%) TE complications (1 stroke, 2 TIA) occurred in LAAO ≥ 80 pts and 4 (3.7%; 1 stroke, 3 TIA) in DOAC ≥ 80 pts ( P = 0.99). The annualized risk of stroke/TIA was 2.5% in the first and 3.5% in the second group. Based on the estimated annual TE risk according to the CHA2DS2-VASc score, the % risk reduction after LAAO and DOAC was 54.5% and 36.4%, respectively. Major bleeding events were 3 [1 intracranial, 2 gastrointestinal (GI)] LAAO ≥ 80 pts, and 3 (2 intracranial, 1GI) in DOAC ≥ 80 pts (2.8% in both groups). Minor bleeding events were significantly higher in DOAC ≥ 80 pts [13.0% ( n = 14) vs. 2.7% ( n = 3); RR: 4.7, 95% CI: 1.4–15.7; P = 0.009]. Conclusions: LAAO was safe and similar to DOAC at preventing ischaemic/major bleeding events in a matched population of patients aged ≥80 years. A significantly higher incidence of minor bleeding events was observed in the DOAC group.